2015
DOI: 10.1093/aje/kwv153
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Quality and Myosteatosis: Novel Associations With Mortality Risk

Abstract: Muscle composition may affect mortality risk, but prior studies have been limited to specific samples or less precise determination of muscle composition. We evaluated associations of thigh muscle composition, determined using computed tomography imaging, and knee extension strength with mortality risk among 4,824 participants aged 76.4 (standard deviation (SD), 5.5) years from the Age, Gene/Environment Susceptibility (AGES)-Reykjavik Study (2002-2006). Cox proportional hazards models were used to estimate haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 40 publications
1
47
0
2
Order By: Relevance
“…Aging in humans is accompanied by a loss of subcutaneous fat but an accumulation of AC and lipids in non-adipose depots, such as bone marrow, liver, and skeletal muscle ( 2 ). Fatty infiltration of skeletal muscle (myosteatosis) has, in particular, been recognized as an important component of aging and frailty ( 21 26 ). Lipid accumulation in muscles of the lower limb is also associated with increased fracture risk in the elderly ( 27 ).…”
Section: Fatty Infiltration In Skeletal Muscle: Cellular and Moleculamentioning
confidence: 99%
“…Aging in humans is accompanied by a loss of subcutaneous fat but an accumulation of AC and lipids in non-adipose depots, such as bone marrow, liver, and skeletal muscle ( 2 ). Fatty infiltration of skeletal muscle (myosteatosis) has, in particular, been recognized as an important component of aging and frailty ( 21 26 ). Lipid accumulation in muscles of the lower limb is also associated with increased fracture risk in the elderly ( 27 ).…”
Section: Fatty Infiltration In Skeletal Muscle: Cellular and Moleculamentioning
confidence: 99%
“…The main consequence is reduced muscle protein synthesis, which also depends on ultrastructural modifications in the number and functionality of mitochondria and intracellular lipid deposition [ 12 , 13 ]. Anabolic resistance also promotes adipose infiltration in the muscle, which contributes to decreased muscle functionality [ 14 , 15 ].…”
Section: Introduction: Sarcopenia and Physical Frailty In Agingmentioning
confidence: 99%
“…Muscle fatty infiltration is closely associated with muscle atrophy, inflammation, insulin resistance, mobility impairments, fracture, and even mortality in the elderly 14, 15, 16, 17. Although the factors leading to fat accumulation in the muscle are not yet fully defined, it has been reported that aging, muscle injury, mechanical unloading, and hormonal imbalance are main causes of ectopic fat formation 1, 2, 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%